ChemInform Abstract: One‐Pot Multicomponent Synthesis of Tetrahydropyridines Promoted by Luminescent ZnO Nanoparticles Supported by the Aggregates of 6, 6‐Dicyanopentafulvene. Issue 24 (June 2015) - Kataria, Meenal; Pramanik, Subhamay; Kumar, Manoj; Bhalla, Vandana
Abstract: A novel 6, 6‐dicyanopentafulvene (DPF) generates and stabilizes luminescent ZnO nanoparticles in THF/H2 O.